Synergic effect of curcumin and its structural analogue (Monoacetylcurcumin) on anti-influenza virus infection - Richart, Sarah M.; Li, Yi-Lin; Mizushina, Yoshiyuki; Chang, Yuan-Yen; Chung, Tse-Yu; Chen, Guan-Heng; Tzen, Jason Tze-Cheng; Shia, Kak-Shan; Hsu, Wei-Li (Yàowu shi͡p︡in fenxi, 2018)
Curcumin (Cur), a polyphenolic compound extracted from spice and common food colourant turmeric, contains versatile bio-activities. Monoacetylcurcumin (MAC), a structural analogue of Cur, differs from Cur by acetyl modification, but retains enone groups. Comparative analysis revealed MAC effectively inhibited influenza virus infection (IAV) to a similar extent as, if not superior to, curcumin. Both compounds mildly reduced viral NA activity. Surprisingly, unlike Cur, the MAC inhibition of IAV did not occur through the blocking of HA activity. However, MAC strongly dampened Akt phosphorylation, the prerequisite signalling for efficient IAV propagation. A much stronger inhibition effect on IAV infection was observed when MAC treatment was in combination with Cur. Collectively, MAC demonstrated clear antiviral activity, and likely inhibited IAV via multiple mechanisms that were not identical to Cur. Importantly, Cur and MAC in combination synergistically inhibited IAV infection. [Display omitted] •As with Cur, MAC effectively inhibited IAV infection.•Combination of curcumin and MAC achieved antiviral synergy.•MAC strongly dampened Akt phosphorylation, the prerequisite signalling for IAV propagation.•MAC inhibited IAV via multiple mechanisms in non-identical ways as Cur.